THE IMPACT OF LIBERALIZATION OF TRADE IN TOURISM SERVICES IN ASEAN TO INDONESIA’S TOURISM COMPETITIVENESS - Basuki Antariksa (Pusbindiklat - LIPI, 2011)
Liberalization of trade in tourism services among ASEAN member countries has been conducted for almost 15 years. However, it is still unclear whether the phenomenon could significantly improve Indonesia’s tourism competitiveness. Through a mixed between literary research and years of personal work experience on international cooperation affairs, a preliminary conclusion shows that the liberalization of trade in tourism services does not directly improve Indonesia’s tourism competitiveness compared to other ASEAN member countries.The result of this research also suggests that government policy based on liberal development theories should be reviewed.